Pengaruh Model Pembelajaran Problem Based Learning (PBL) Berbasis RQA terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Siswa dengan Menggunakan Aplikasi Wordwall di SMP Negeri 11 Samarinda - Salsabila Desvika Nurfadhila; Elsje Theodora Maasawet; Sri Purwati; Akhmad Akhmad; Suparno Putera Makkadafi (Biocaster : Jurnal Kajian Biologi, 2025)
The results of observations conducted by researchers on February 2, 2025 with teachers at SMP Negeri 11 Samarinda show several problems, including the low critical thinking skills of students, learning outcomes that are not optimal, and the lack of use of digital media and innovative learning models. This condition causes students to have difficulty in understanding the learning material delivered by the teacher. This study aims to determine the influence of the Problem Based Learning (PBL) learning model based on Reading, Questioning, and Answering (RQA) on students' critical thinking skills and learning outcomes by using the Wordwall application at SMP Negeri 11 Samarinda. The research method used is a correlational method with a quantitative approach. The sampling technique was carried out by purposive sampling with classes VII-I and VII-H as research samples. Data analysis using t-test. After applying the RQA-based PBL learning model in class VII-H as an experimental class and given a critical thinking ability test and a learning outcome test, the average score of the experimental class was higher than the control class. The results of the data analysis showed that in the control class, the level of significance of critical thinking skills was 0.000 < 0.05 and learning outcomes were 0.002 < 0.05. This shows that the application of the RQA-based PBL learning model has a significant effect on improving students' critical thinking skills and learning outcomes on ecology and biodiversity materials at SMP Negeri 11 Samarinda. These findings prove that the application of the RQA-based PBL model is effective in improving students' critical thinking skills and learning outcomes.